(untitled) (Journal of actual problems of jurisprudence, 2019)
One of the most pressing problems of our time is that of the religious dimension of human life, which from the point of view of the legal world, and carries out its legal science is formulated as a problem of the creation of a secular state. The author considers some of the problems of constitutionalism and ensure secular state of Kazakhstan.